Auditoría de los Estados Financieros una Herramienta para Controlar la Evasión y la Corrupción en el Sector Público (2021)
This article demonstrates, based on the implementation of an audit of the financial statements, how it can become a fundamental part so that in the first place it controls evasion and corruption in organizations and public entities in order to provide a context without corruption, without However, it is worth mentioning that also thanks to the management of the NIA-ES, in conjunction with the IFAC (International Federation of Accountants) in this way we can find the achievement of objectives such as the minimization of risks concerning fraud. Understand how important is this implementation of the audit that must be carried out to public entities, to find the quality of financial information and thus be able to distribute resources to the community in a fair and equitable way avoiding corruption in Colombia. With reference to the aforementioned, the ISSAIs (International Standards Of Supreme Audit Institutions) form a set of norms where part of them deal with all the most used prerequisites for the scope of a correct audit in the public sector and thus the Treasury is supported by these regulations, therefore, Colombia has this protection in the financial statements and in the accounting, thus reflecting the economic reality of these public sector entities. Likewise, according to the statistics before the OECD and as a subsequent result, it has been found that Colombia has significantly improved its qualification nationally and internationally, thus generating adequate and pertinent training for all personnel, such as officials who have violated the law for interests unrelated to what should be invested all the resources of the Colombian nation in auditing issues, their implementation, among others.